Expertenempfehlung zur Magnetresonanztomographie bei Muskelerkrankungen - Zeng, Rachel; Schlaeger, Sarah; Türk, Matthias; Baum, Thomas; Deschauer, Marcus; Janka, Rolf Matthias; Karampinos, Dimitrios; Kassubek, Jan; Keller-Yamamura, Sarah; Kornblum, Cornelia; Lehmann, Helmar; Lichtenstein, Thorsten; et al. (Der Nervenarzt, 2024)
Background: Magnetic resonance (MRI) imaging of the skeletal muscles (muscle MRI for short) is increasingly being used in clinical routine for diagnosis and longitudinal assessment of muscle disorders. However, cross-centre standards for measurement protocol and radiological assessment are still lacking. Objectives: The aim of this expert recommendation is to present standards for the application and interpretation of muscle MRI in hereditary and inflammatory muscle disorders. Methods: This work was developed in collaboration between neurologists, neuroradiologists, radiologists, neuropaediatricians, neuroscientists and MR physicists from different university hospitals in Germany. The recommendations are based on expert knowledge and a focused literature search. Results: The indications for muscle MRI are explained, including the detection and monitoring of structural tissue changes and oedema in the muscle, as well as the identification of a suitable biopsy site. Recommendations for the examination procedure and selection of appropriate MRI sequences are given. Finally, steps for a structured radiological assessment are presented. Conclusions: The present work provides concrete recommendations for the indication, implementation and interpretation of muscle MRI in muscle disorders. Furthermore, it provides a possible basis for the standardisation of the measurement protocols at all clinical centres in Germany.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Diagnostics; Muscle MRI; Myopathy; Myositis; Semi-quantitative assessment scales